2020
DOI: 10.1177/1082013220957529
|View full text |Cite
|
Sign up to set email alerts
|

Effects of ultraviolet-C light-emitting diodes at 275 nm on inactivation of Alicyclobacillusacidoterrestris vegetative cells and its spores as well as the quality attributes of orange juice

Abstract: Alicyclobacillus acidoterrestris is a thermoacidophilic, spore-forming bacillus. A. acidoterrestris and its spores can survive in pasteurized juices and cause microbial spoilage. In this work, the effects of ultraviolet-C light-emitting diodes at 275 nm on the inactivation of A. acidoterrestris vegetative cells and its spores in commercial pasteurized orange juice were studied. Meanwhile, the effects of ultraviolet-C light-emitting diodes on the quality attributes of the orange juice were also investigated. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 44 publications
0
2
0
Order By: Relevance
“…Torkamani and Niakousari [83] showed a D10 value in orange juice of 105 mJ/cm 2 . Zhai et al [41] obtained an average value of 56 (mJ/cm 2 ) on the inactivation of Alicyclobacillus acidoterrestris in orange juice, and Baysal et al [13] a value of 9.55 (mJ/cm 2 ) on the inactivity of Alicyclobacillus acidoterrestris in apple juice, among others. On the other hand, Table 3 presents the goodness of fit in terms of R 2 .…”
Section: Microbial Inactivation Kinetics and Weibull Modelingmentioning
confidence: 99%
See 2 more Smart Citations
“…Torkamani and Niakousari [83] showed a D10 value in orange juice of 105 mJ/cm 2 . Zhai et al [41] obtained an average value of 56 (mJ/cm 2 ) on the inactivation of Alicyclobacillus acidoterrestris in orange juice, and Baysal et al [13] a value of 9.55 (mJ/cm 2 ) on the inactivity of Alicyclobacillus acidoterrestris in apple juice, among others. On the other hand, Table 3 presents the goodness of fit in terms of R 2 .…”
Section: Microbial Inactivation Kinetics and Weibull Modelingmentioning
confidence: 99%
“…Moreover, Ngadi et al [78] studied apple juice and applied a UV fluence of 300 mJ/cm 2 for 16 min to achieve a logarithmic reduction of 4.2 CFU/mL in E. coli O157:H7 ATCC 35150. Zhai et al [41] reported that UV-C-LED irradiation reduced the population of Zygosaccharomyces rouxii in apple juice at 4.86 log CFU/mL at 800 mJ/cm 2 . These authors concluded that the treatment has potential application in the juice processing industry.…”
Section: Microbial Inactivation Kinetics and Weibull Modelingmentioning
confidence: 99%
See 1 more Smart Citation
“…41 Studies have documented the successful use of UV-C radiation (100-280 nm) in decontaminating bacterial vegetative spores of Alicyclobacillus acidoterrestris. 42 Nakpan et al reported that bacterial spores exhibit an order of magnitude greater sensitivity to UV radiation compared to Aspergillus fumigatus spores. 20 As depicted in Fig.…”
Section: Effect Of Uv Radiation On Fungal Spores (Expressed By Metabo...mentioning
confidence: 99%
“…Zhai et al (2020) demonstrated the reduction of A. acidoterrestris vegetative cells and spores in commercial pasteurized orange juice with the application of UV‐C LEDs at 275 nm. The growth temperature and pH for A. acidoterrestris ranges from 20°C to 70°C, and 2.0 to 7.0, respectively (Grande et al, 2005).…”
Section: Leds For Food and Beverage Preservationmentioning
confidence: 99%